(untitled) (Revista Innova Educación, 2021)
This research aimed to implement a Peace Education Project (PEP) in a first-grade classroom of a primary school located in San Cristobal de las Casas, Chiapas, Mexico. The intervention promoted a set of prosocial competencies in students, teachers and families; for this universal and focused strategies were developed. A mixed approach was used, with evaluations before and after. Information was collected through participatory action-research. Some findings indicate that systematic PEPs in the classroom decrease violence and strengthen prosociability. There was a reduction in the school violence index from 1.12 to 1.10 and an increase in student prosociability from 3.34 to 3.70. The strategies favorably affected the maintenance of a school climate of cordiality, greater empathy, assertiveness, better management of emotions and an increase in friendship networks.